Analisis Manajemen Risiko Pengelolaan Sumber Daya Manusia (STUDI KASUS COFFEE SHOP 48 STREET TASIKMALAYA) - Aditya Akbar Prasetyo; Jesika Tamaria; Muhammad Ditto Marcelino; Nina Nuraeni; Reyhan Arya Nugraha; Syifa Nurul Aulia; Syti Maesaroh Maesaroh (STIE Wiyatamandala, 2023)
Human resources is one important aspect that must be possessed by everycompany. In supporting the success of the company's operations, managementneeds to be carried out so that the existing system can be well organizedaccording to the company's expectations. In this study using a case study atCoffee Shop 48 Street Tasikmalaya. The purpose of this research is to find out thehuman resource management system and the risks that exist in the company. Inthis study, a qualitative approach was used with a descriptive research type, andthe collection technique used was direct interviews with managers and siteobservations. The results of interviews through the manager of the Coffee Shop 48Street Tasikmalaya found several risks related to human resource management which were then analyzed using the checklist method, and in this analysis, riskidentification, risk assessment, and risk control were carried out. The results ofthis study are that Coffee Shop 48 Street Tasikmalaya need to improve humanresource management to improve an organized performance environment